Diffuse alveolar haemorrage as initial presentation of systemic lupus erythematosus: a case report. (March 2018) - Cucuzza, M E; Marino, S D; Schiavone, L; Smilari, P; Filosco, F; Barone, P
Diffuse alveolar haemorrhage (DAH) is a rare life-threatening complication of systemic lupus erythematosus (SLE), associated with high mortality rates. It usually occurs in patients with an established diagnosis of SLE. It has been reported as the initial presentation of SLE in 11−20% of cases. It occurs most frequently in females. We describe the case of a child, aged 14 years, with fever, asthenia, haemoptysis, dyspnea, anaemia, increased inflammatory markers, positivity to ANA, nDNA, direct Coombs tests, anticardiolipin antibodies and complement factors consumption. Computed tomography (CTscan) of the chest showed bilateral pulmonary alveolar infiltrates. He also developed renal involvement with nephritis later in the course of the disease. He was started on the treatment approved by the Euro Lupus Protocol for critical patients. After starting Mycophenolate Mofetil the clinical and radiological features were improved as was the survival outcome.